Neuroanatomical anomalies of dyslexia: Disambiguating the effects of disorder, performance, and maturation. (29th January 2016) - Xia, Zhichao; Hoeft, Fumiko; Zhang, Linjun; Shu, Hua
Abstract: An increasing body of studies has revealed neuroanatomical impairments in developmental dyslexia. However, whether these structural anomalies are driven by dyslexia (disorder-specific effects), absolute reading performance (performance-dependent effects), and/or further influenced by age (maturation-sensitive effects) remains elusive. To help disentangle these sources, the current study used a novel disorder (dyslexia vs. control) by maturation (younger vs. older) factorial design in 48 Chinese children who were carefully matched. This design not only allows for direct comparison between dyslexics versus controls matched for chronological age and reading ability, but also enables examination of the influence of maturation and its interaction with dyslexia. Voxel-based morphometry (VBM) showed that dyslexic children had reduced regional gray matter volume in the left temporo-parietal cortex (spanning over Heschl's gyrus, planum temporale and supramarginal gyrus), middle frontal gyrus, superior occipital gyrus, and reduced regional white matter in bilateral parieto-occipital regions (left cuneus and right precuneus) compared with both age-matched and reading-level matched controls. Therefore, maturational stage-invariant neurobiological signatures of dyslexia were found in brain regions that have been associated with impairments in the auditory/phonological and attentional systems. On the other hand, maturational stage-dependent effects on dyslexia were observed in three regions (left ventral occipito-temporal cortex, left dorsal pars opercularis and genu of the corpus callosum), all of which were previously reported to be involved in fluent reading and its development. These striking dissociations collectively suggest potential atypical developmental trajectories of dyslexia, where underlying mechanisms are currently unknown but may be driven by interactions between genetic and/or environmental factors. In summary, this is the first study to disambiguate maturational stage on neuroanatomical anomalies of dyslexia in addition to the effects of disorder, reading performance and maturational stage on neuroanatomical anomalies of dyslexia, despite the limitation of a relatively small sample-size. These results will hopefully encourage future research to place greater emphasis on taking a developmental perspective to dyslexia, which may, in turn, further our understanding of the etiological basis of this neurodevelopmental disorder, and ultimately optimize early identification and remediation. Highlights: This study disentangled different sources of anomalies in dyslexic children. Persistent volume decreases were found in phonology and attention related regions. There were areas that showed maturation-sensitive impairments in dyslexia. Dyslexia is characterized by both persistent and altered neural deficits.